INTERNATIONAL HUMAN RIGHTS AND TRANSITIONAL JUSTICE: BRIDGING THE GAP BETWEEN LAW AND PRACTICE - 1. Ms. Savita Panwar , 2. Dr. Suman Paliwal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This paper investigates the relationship between international human rights and transitional justice, focusing on the discrepancies between legal standards and their implementation in post-conflict environments. Although international human rights law offers a foundational framework for justice, transitional justice initiatives frequently encounter difficulties in achieving effective application. The research underscores the necessity of closing this gap, arguing that human rights principles can bolster the credibility of transitional justice processes. The paper identifies achievements and challenges in transitional justice efforts by analyzing significant theoretical concepts, including complementarity and interdependence, alongside various case studies. The article proposes a cohesive, context-aware strategy that takes into account both international guidelines and local conditions, aiming to promote enduring peace, accountability, and reconciliation.